Detection and molecular characterization of enteric viruses in commercial birds - Duque, David Isaías De la Torre (2019)
Enteric viruses in commercial birds are associated with infections that affect the health and productive rates of animals, causing economic losses for the poultry industry in Brazil and worldwide. The objective of this study is to identify the main enteric viruses that infect commercial poultry flocks in Brazil and in some cases in neighboring countries where the poultry industry is an important factor for economic development. For this study, frozen samples of bird organs from different states of Brazil and Ecuador were used, as well as results previously obtained by the avian disease diagnosis service of the Laboratory of Avian Pathology at the School of Veterinary Medicine and Animal Sciences of the University of São Paulo. Diagnoses were performed through conventional polymerase chain reaction (PCR) and reverse transcription-PCR, and the characterization of different viruses was performed by sequence analysis of specific genes from randomly selected samples from each virus diagnosed. The results provide important information about virus serotypes and their geographic distribution within the Brazilian territory. Three serotypes (8a, 8b, and 11) of fowl adenovirus group I (FAdVI) were found in digestive, respiratory, and immunological organs, including the heart and kidneys. In addition to FAdV-I, during the period from 2010 to 2017, chicken parvovirus, chicken astrovirus, avian nephritis virus, infectious bronchitis virus, avian reovirus, and avian rotavirus were found in samples from 11 different Brazilian states (Mato Grosso, Goias, Piaui, Ceara, Paraiba, Pernambuco, Bahia, Minas Gerais, Espirito Santo, São Paulo, and Santa Catarina). Chicken parvovirus was molecularly diagnosed for the first time in samples of commercial birds from Ecuador. Tremovirus A (AEV) was diagnosed in outbreaks of avian encephalomyelitis in broilers during the period from 2006 to 2015, even though vaccination in breeders is included in the regimen to prevent the vertical transmission of this virus. These results demonstrate the diversity of viruses that affect commercial birds individually or in combination with other viruses, while the exact role of each one within enteric diseases is still not well understood, requiring experimental studies to achieve more knowledge about the pathogenesis of these etiological agents.